Ethnophilosophy and Public Morality in an African Tribe - Dike, Uche A. (Scientific Research, 2015)
The paper is a field research work delving into the ethnophilosophy of Ogba religion. Its focal point is on the people’ worldview, as it pertains to life, public morality, value and Adamic sins in Ogba Land Rivers State, Nigeria. It posits that the natural or physical world is an extension of the supernatural or the spiritual and must be understood in that sense if a valid explanation about Ogba people’ vision of life must be sufficiently compatible with their cosmology. In the area of public morality, the ethnophilosophy of Ogba people is holistic and integrated. Thus, anti social behaviours or abominations known as Adamic sins in this paper are viewed as disruptive of public order and morality. In this wise the people’s weltanschauung provided value essence as a foundation for existence. Hence, inviolable sanctity of human life and good moral character ranked to be the highest value in Ogba Land.
Keywords: Ogba Land; Religion; Public; Moral; Value; Adamic Sins